Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Kinerja Keuangan Pemerintah Daerah Dengan Belanja Sosial Sebagai Variabel Intervening - Yunita Widya Rahayu; Tatas Ridho Nugroho; Nurdiana Fitri Isnaini; Hartono Hartono (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to test the effect of the independent variable on the dependent variable and test the intervening variable that can support the relationship of the independent variable to the dependent variable. The independent variables used in this study are Regional Original Income (PAD) and equalization funds, the dependent variable is financial performance, and the intervening variable used is social assistance spending. The sampling method used is the saturated sampling method. The total population in this study is 7 Regency / City Governments incorporated in the Gerbangkertosusila area in 2018-2022. Hypothesis testing in this study used Partial Least Square (PLS). The results of this study show that Regional Original Revenue (PAD) has a positive effect on financial performance. Meanwhile, the balancing fund and social assistance expenditure did not affect financial performance, and social assistance spending proved unable to support the relationship between Regional Original Revenue (PAD) and the balancing fund on financial performance. Keywords: Local original revenue, equalization fund, social assistance expenditure, regional financial performance.